2015
DOI: 10.1638/2014-0201r1.1
|View full text |Cite
|
Sign up to set email alerts
|

CUTANEOUS EPITHELIOTROPIC T-CELL LYMPHOMA WITH METASTASES IN A VIRGINIA OPOSSUM (DIDELPHIS VIRGINIANA)

Abstract: A 2-yr-old, captive, intact female Virginia opossum ( Didelphis virginiana ) with a 7-mo history of ulcerative dermatitis and weight loss was euthanatized for progressive worsening of clinical signs. Initially the opossum was treated with several courses of antibiotics, both topically and systemically; systemic nonsteroidal anti-inflammatory medication; and, later, systemic glucocorticoids, with no improvement in clinical signs. Histopathologic samples of skin lesions taken 3 mo into the course of disease reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…2,14,23 In our study, the majority of the documented neoplasms, 82% (14 of 17) were malignant, which is consistent with previous reports in the literature. 2,10,14,16,17,21 Squamous cell carcinoma has been previously reported in the oral cavity of a Virginia opossum and was located on the tongue, 14 whereas it was located on the maxilla in case 12 in our study. The previously reported basal cell tumor 22 may have been a trichoblastoma, as in the current study, as the microscopic description was consistent and basal cell tumors have become further classified.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…2,14,23 In our study, the majority of the documented neoplasms, 82% (14 of 17) were malignant, which is consistent with previous reports in the literature. 2,10,14,16,17,21 Squamous cell carcinoma has been previously reported in the oral cavity of a Virginia opossum and was located on the tongue, 14 whereas it was located on the maxilla in case 12 in our study. The previously reported basal cell tumor 22 may have been a trichoblastoma, as in the current study, as the microscopic description was consistent and basal cell tumors have become further classified.…”
supporting
confidence: 50%
“…Because neither CD20 nor CD79 identified normal B-lymphocytes in opossums, the possibility remains that the neoplasm in the heart and kidney was a lymphosarcoma of B-cell origin. Cutaneous epitheliotropic T-cell lymphoma with visceral metastasis was previously reported in a single Virginia opossum, 10 and lymphosarcoma, unknown B-or T-cell origin, was previously diagnosed in 2 Virginia opossums. 2,16 Neoplasia is common in other species of opossums and possums, as well.…”
mentioning
confidence: 99%
“…CEL is a subgroup of epitheliotropic lymphoma, which is a rare neoplasm of T cells with tropism to epidermis and adnexal structures . CEL is characterized by an abundance of CD3+ T cells and their migration into the epidermis and adnexal structures of the skin, with the presence of infiltrates such as plasma cells, eosinophils, histiocytes, and frequent clustering of T lymphocytes around the dendritic cells forming Pautrier's microabscesses (not present in the this case) . In several studies analyzing CELs, canid species have been shown to illustrate the CD3+CD4−CD8+ phenotype .…”
Section: Discussionmentioning
confidence: 99%
“…CEL has been widely reported in dogs and cats . However, reports of CEL in other species are rare and include cows, hamsters, mice, and single reports in a rat, ferret, squirrel, coati, cuscus, chipmunk, zebrafish, hedgehog, Tasmanian devil, opossum, marsh rice rat, and alpaca . There are currently no reports of CEL in NHPs.…”
Section: Discussionmentioning
confidence: 99%
“…Three species of fur mites were found on the opossum (Stankiewicz et al., 1996). Neoplastic cells consistent with lymphoma were found in the haired skin of the forearm, axilla and pelvic limbs of a female Virginia opossum (Higbie et al., 2015). The ringworm caused by T .…”
Section: Introductionmentioning
confidence: 99%